2009
DOI: 10.1063/1.3123164
|View full text |Cite
|
Sign up to set email alerts
|

Contact resistance in carbon nanostructure via interconnects

Abstract: We present an in-depth electrical characterization of contact resistance in carbon nanostructure via interconnects. Test structures designed and fabricated for via applications contain vertically aligned arrays of carbon nanofibers (CNFs) grown on a thin titanium film on silicon substrate and embedded in silicon dioxide. Current-voltage measurements are performed on single CNFs using atomic force microscope current-sensing technique. By analyzing the dependence of measured resistance on CNF diameter, we extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 12 publications
2
38
0
Order By: Relevance
“…However, contact resistance between CNT or CNF and metal remains a major challenge [2][3][4][5][6][7]. Moreover, contact resistance tends to dominate the total test device resistance [6,7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, contact resistance between CNT or CNF and metal remains a major challenge [2][3][4][5][6][7]. Moreover, contact resistance tends to dominate the total test device resistance [6,7].…”
mentioning
confidence: 99%
“…Moreover, contact resistance tends to dominate the total test device resistance [6,7]. Previously, Wu [6] and Li [7] developed methods to extract contact resistance between CNF and underlayer metal in vertical via structures.…”
mentioning
confidence: 99%
“…Though field emission from carbon fibers has been known since 1973 [23], it was first in 1995 when a carbon nanotube based field emission electron source has been reported [30]. The device had an array of vertically aligned current density and stability of emission (figure 2.4).…”
Section: Carbon Nanotubes In Field Emittersmentioning
confidence: 99%
“…Recently, it has also been shown that the contact resistance has a diameter dependant component, which is inversely related to the resistance term [30]. Thus, it is expected that thinner CNTs will have higher contact resistance leading to reduced emission response.…”
Section: 6: Field Emission Responses Of Mwcnt Emitters On Ti-intermementioning
confidence: 99%
See 1 more Smart Citation